All You Need Is Love: The Importance of Partner and Family Relations to Highly Creative Individuals' Well‐Being and Success. (9th May 2018) - Lebuda, Izabela; Csikszentmihalyi, Mihaly
Abstract: The aim of the article was to investigate how the family life of highly creative individuals—mainly marriages or romantic relationships—is related to their sense of success and well‐being. Previous studies have led to conflicting conclusions. The predominant finding has been that marriage and family constitute an obstacle to creative potential development. Other studies have demonstrated that, regardless of gender, creators lead satisfying family lives, which contributes to their well‐being. The study presented in this paper is based on the grounded theory methodology and triangulates two sources: interviews with prominent creators from the USA conducted years ago (Csikszentmihalyi, 1996, N  = 91) and interviews with recognized contemporary Polish artists and scientists ( N  =   34). Based on interactions between the interviewees' perception of themselves as creators and their perception of gender and family roles, the authors identify and discuss five types of relationship between creators' family life and work. They also discuss the factors that hinder or facilitate creators' satisfactory functioning in both areas in each of the five types of relationship.